Applying Organizational Support Lenses for Employee Retention: The Role of Supervisor Support and Compensation Fairness - Oladimeji, Kazeem Adebayo (Journal of Technology Management and Business, 2024)
Employee retention is critical, yet organizations face challenging talent markets and increasing turnover costs from departing staff. This study examines drivers of retention for professional workers to isolate actionable focus areas for organizations. Drawing on organizational support theory, perceived organizational support, compensation fairness, and quality leader-member exchange relationships are hypothesized to reduce turnover intentions. Survey data from 120 employees confirmed perceived organizational support as the strongest predictor, followed by compensation equity and supervisor support. All three fulfil socioemotional needs that build affective commitment and loyalty when present. Practical recommendations center on monitoring support perceptions through pulse surveys, purposeful communications conveying care for employees, and leader training on nurturing developmental relationships. Investing in perceived support elements represents a high-yield, affordable retention strategy. These findings refine broader retention drivers, spotlighting the centrality of care and inclusion assurances for anchoring talent. Limitations around generalizability and cross-sectional data point to useful future research directions.